Wheat Disease Resistance Genes and Their Diversification Through Integrated Domain Fusions - Andersen, Ethan J.; Nepal, Madhav P.; Purintun, Jordan M.; Nelson, Dillon; Mermigka, Glykeria; Sarris, Panagiotis F. (Frontiers in Genetics, 2020)
Plants are in a constant evolutionary arms race with their pathogens. At the molecular level, the plant Nucleotide-binding Leucine-rich repeat Receptors (NLRs) family has co-evolved with rapidly evolving pathogen effectors. While many NLRs utilize variable Leucine-Rich Repeats (LRRs) to detect effectors, some have gained Integrated Domains (IDs) that may be involved in receptor activation or downstream signaling. The major objectives of this project were to identify NLR genes in wheat (Triticum aestivum L.) and assess IDs associated with immune signaling (e.g. kinase and transcription factor domains). We identified 2,151 NLR-like genes in wheat, of which 1,298 formed 547 gene clusters. Among the non-Toll/interleukin-1 receptor NLR (non-TNL)-like genes, 1,552 encode LRRs, 802 are Coiled-Coil (CC) domain-encoding (CC-NBS-LRR or CNL) genes, and three encode Resistance to Powdery mildew 8 (RPW8) domains (RPW8-NBS-LRR or RNL). The expansion of the NLR gene family in wheat is attributable to its origin by recent polyploidy events. Gene clusters were likely formed by tandem duplications, and wheat NLR phylogenetic relationships were similar to those in barley and Aegilops. We also identified wheat NLR-ID fusion proteins as candidates for NLR functional diversification, often as kinase and transcription factor domains. Comparative analyses of the IDs revealed evolutionary conservation of more than 80% amino acid sequence similarity. Homology assessment indicates that these domains originated as functional non-NLR-encoding genes that were incorporated into NLR-encoding genes through duplication events. We also found that many of the NLR-ID genes encode alternative transcripts that include or exclude IDs, a phenomenon that seems to be conserved among species. To verify this, we have analyzed the alternative transcripts that include or exclude an ID of an NLR-ID from another monocotyledon species, rice (Oryza sativa). This indicates that plants employ alternative splicing to regulate IDs, possibly using them as baits, decoys, and functional signaling components. Genomic and expression data support the hypothesis that wheat uses alternative splicing to include and exclude IDs from NLR proteins.